Maceration Time Affects the Efficacy of Borage Extracts as Potential Biostimulant on Rocket Salad - Giulia Franzoni (MDPI AG, 2021)
The efficacy of plant-based biostimulants lays on the extraction of bioactive compounds that can trigger positive biological responses in plants. Their use has been increasing for lowering the production costs, enhance the yield and the stress tolerance, and improve the cropping systems’ sustainability. The aim of this work was to investigate the effect of maceration time on borage extracts, subsequently sprayed on rocket plants hydroponically grown. A preliminary test was also assessed to evaluate the extracts’ effect on seeds germination. Borage leaves and flowers were separated and macerated in the same conditions for different times. The obtained borage extracts were applied two times during the cultivation of rocket plants. The yield was not affected by the treatments, while the quality of leafy vegetables was improved. The results indicated that the flower extracts (FE) were more active than leaf extracts (LE) in stimulating the crop response. Promising results were observed on the nitrate assimilation, with reduced accumulation in the edible and commercial parts. Non-destructive analysis revealed that electron transport rates were significantly higher in treated plants. Biostimulant effects were also confirmed by the lowering of sucrose and sugars content in the treated plants and by a general increment of secondary metabolites.